Theology in Transposition : A Constructive Appraisal of T. F. Torrance - Habets, Myk (Minneapolis, MN : Fortress Press, 2013)
"T. F. Torrance was one of the most significant English-language theologians of the twentieth-century known extensively for his curatorship of the English translation of Barth's Church Dogmatics but also for his own prodigious theological scholarship. The complexity and astonishing breadth of Torrances output, however, have made assessment and appropriation markedly difficult. This volume seeks to rectify that lack of assessment through careful exposition of the vital centers and interconnections within Torrances theology alongside constructive appraisal and critique of his contributions to contemporary theology" -- Publisher description
Part I. The architectonic nature of Torrance's scientific Christian dogmatics : essays on method. Who is Thomas Forsyth Torrance? -- Scientific theology : an theological science -- Natural theology : and a theology of nature -- Realist theology : and theological realism -- Part II. Select themes within Torrance's theological oeuvre : essays on content. Mystical theology : reading Torrance as a mystical theologian sui generis -- Integrative theology : God, world, humanity -- Christocentric theology : the fallen humanity of the Son of God -- Postscript: Torrance for the twenty-first century
Includes bibliographical references (pages 199-220) and index
Keywords: Torrance, Thomas F. -- 1913-2007; Philosophical theology